Type 2 Diabetes Alters Vascular Cannabinoid Receptor 1 Expression, Phosphorylation Status, and Vasorelaxation in Rat Aorta - Enrique Sánchez-Pastor; Xóchitl Trujillo; Christian Ramos-Flores; Mónica Ríos-Silva; Felipa Andrade; Yolitzy Cárdenas; Elena Castro; Zorayda Urzúa; Oscar Newton-Sánchez; Miguel Huerta (Molecules, 2020)
Previous studies have suggested a role of the endocannabinoid system in metabolic diseases, such as diabetes. We investigated the effect of diabetes on cannabinoid receptor type 1 (CB1) expression and cannabinoid-induced vasorelaxation in rat aorta rings. Aortas from healthy rats and from rats with experimentally induced diabetes were used to compare the vasorelaxant effect of the cannabinoid agonist arachidonylcyclopropylamide (ACPA) and CB1 expression and localization. After 4–8 weeks of diabetes induction, CB1 receptor expression and CB1 phosphorylation were higher in aortic rings, in association with greater vasorelaxation induced by the CB1 agonist ACPA compared to healthy rats. The vasorelaxant effect observed in healthy rats is similar throughout the study. Further studies are needed to elucidate the implications of CB1 receptor overexpression in diabetes and its influence on the progression of the cardiovascular complications of this metabolic disease.